COST AND TIME CONTROL STUDY USING EARNED VALUE MANAGEMENT METHODS IN FENCE AND GATE CONSTRUCTION PROJECTS POLYTECHNIC MUARA TEWEH - Shakilla, Juniandra Nufusyah; Widiastuti, Endah (CERUCUK, 2026)
This research focuses on controlling costs and time in the Fence and Gate Construction Project at Muara Teweh Polytechnic using the Earned Value Management method. This research aims to evaluate project performance by analyzing plan schedule data, weekly progress reports, and project budget (CBP) to assess the actual status of project costs and schedule. The results of direct interviews showed that the project experienced delays due to shortages of materials, delays in the arrival of materials, and unfavorable weather conditions, which caused deviations from the planned schedule. The analysis uses three main indicators: BCWS, BCWP, ACWP. The results show that from week 8 to week 15, the project experienced delays, although it did not cause cost overruns during the 16 week duration. This study concludes that the implementation of EVM can serve as a valuable reference for anticipating potential cost and time deviations in future project phases. Keywords: Earned Value Management, Time Performance, Cost Performance